Kajian Angkutan Sedimen Di Sungai Pabelan, Kabupaten Magelang, Jawa Tengah - Fauziyah, Risky; Kironoto, Bambang Agus; Legono, Djoko (Universitas Muhammadiyah Yogyakarta, 2018)
Pabelan River is one of the rivers in the western slopes of mount Merapi located in Magelang Regency, Central Java province. Pabelan River has watersheds ± 84,70 km2 with the main river length ± 28,40 km2. The purpose of this research was to estimate the amount of sediment transport that occurred at the point of view in the Pabelan River and to know estimate of sediment balance that occurred at the point of view in the Pabelan River. This research was conducted to find out the sediment balance in the Pabelan River whether going on degradation, aggradation, or experience the equilibrium transport. Calculation of sediment balances based on the volume of sediment transport entering at the location selected. Based on the results of sediment transport analysis using MPM, EINSTEIN, DU BOYS and ROTTNER formula, the largest sediment transport volume occurred in PA-C 5 = 4850,592 m3/m/flood, 305,8398 m3/m/flood, 20321,979 m3/m/flood and 80274,221 m3/m/flood, while the result of calculation based on formula FRIJLINK largest sediment transport volume occurred at PA-C 3 = 3654,817 m3/m/flood. To obtain the result of equilibrium sediment that occurred in the river of research is by using the five formula with the condition of the river that occurred aggradation and degradation with the biggest condition is the result of calculation with the formula ROTTNER for aggradation occurs in PA-C X Prumpung amount of 47272,806 m3/m/s with increase river bed amount of 13,504 m and degradation occurred at PA-C 5 -47468,692 m3/m/s with decrease at river bed -23,698 m.